Relationship between the level of mixed chemicals in male urine and the prevalence of male cancers, especially prostate cancer - Zhang, Bin; Sun, Hao; Zhu, Bin; Wang, Mengmeng; Zuo, Bingli; Dai, Jiuming (Frontiers in Public Health, 2025)
ObjectivesThe aim of this study was to investigate the relationship between mixed chemicals in urine and the prevalence of cancers in men.MethodsA total of 1,068 male subjects were included in this study. Analyses were performed by several analytical methods to ensure the stability of the results: one-way analysis, WQS analysis, Qgcomp analysis, BKMR analysis, and Restricted Cubic Spline (RCS).ResultsIn the final adjusted model, each 1 increase in ln-transformed BPS increased the risk of developing cancerous prostate by 49% (95% CI: 1.00–2.20). The results of multiple sensitivity analyses by WQS and Qgcomp showed that the mixed chemicals was positively correlated with the prevalence of cancers and prostate cancer in men. In the final adjusted model, each quartile increase in the WQS index was associated with a 78% (OR: 1.78, 95% CI: 1.10–2.87) increase in the risk of cancers and a 148% (OR: 2.48, 95% CI: 1.07–5.71) increase in the risk of prostate cancer. Each quartile increase in the Qgcomp index was associated with a 59% (OR: 1.59, 95% CI: 1.09–2.33) increase in the risk of cancers, and a 105% (OR: 2.05, 95% CI: 1.04–4.06) increase in the risk of prostate cancer.ConclusionIn conclusion, this study showed a positive correlation between the concentrations of the three groups of mixed chemicals in urine and the prevalence of cancers in men, as well as a positive correlation with the prevalence of prostate cancer.